Propensity of using Harmful Gas Controller and Oxygen Supplier on the Basis of Fish Farmers Age, Educational Status and Landownership of Six Upazilas in Noakhali District, Bangladesh (Global Journal of Science Frontier Research, 2014)
The intensity of aquaculture is increasing day by day in Bangladesh. To meet the increasing demand new technologies are being used to enhance production. Recently the use of fish medicines in aquaculture is also seen among the farmers of our country. In the present study, the propensity of using harmful gas controller and oxygen supplier on the basis of farmers' age, educational status and land ownership were studied. The study was conducted in six upazilas of Noakhali district, Bangladesh. Data were collected through questionnaire survey of 77 fishermen by interviewing with them and discussing with the upazila fisheries officer, retailers of fish medicines and representatives of pharmaceutical companies and market survey.
Keywords: harmful gas controller; oxygen supplier; educational status; landownership